Neuroprotective and anti-epileptic potentials of genus Artemisia L. - Sailike, Bayan; Omarova, Zhannur; Jenis, Janar; Adilbayev, Altynay; Akbay, Burkitkan; Askarova, Sholpan; Jin, Wei-Lin; Tokay, Tursonjan (Frontiers in Pharmacology, 2022)
The Genus Artemisia L. is one of the largest genera in the Asteraceae family growing wild over in Europe, North America, and Central Asia and has been widely used in folk medicine for the treatment of various ailments. Phytochemical and psychopharmacological studies indicated that the genus Artemisia extracts contain various antioxidant and anti-inflammatory compounds and possess antioxidant, anti-inflammatory, antimicrobial, antimalarial, and antitumor activity. Increasing experimental studies have demonstrated that many Artemisia extracts offer a great antiepileptic potential, which was attributed to their bioactive components via various mechanisms of action. However, detailed literature on the antiepileptic properties of the genus Artemisia and its mechanism of action is segregated. In this review, we tried to gather the detailed neuroprotective and antiepileptic properties of the genus Artemisia and its possible underlying mechanisms. In this respect, 63 articles were identified in the PubMed database, from which 18 studies were examined based on the pharmacological use of Artemisia in epilepsy. The plant extracts have been reported to possess antiepileptic and neuroprotective properties by modulating oxidative stress, protecting mitochondrial membrane potential required for ATP production, up-regulating GABA-A receptor and nACh receptor activities, and interfering with various anti-inflammatory and anti-apoptotic pathways, such as mitochondrial apoptosis pathway, ERK/CREB/Bcl-2 and Nrf2 pathways. This review provides detailed information about some species of the genus Artemisia as potential antiepileptic agents. Hence, we recommend further investigations on the purification and identification of the most biological effective compounds of Artemisia and the mechanisms of their action to cure epilepsy and other neurological diseases.